2020
DOI: 10.1016/j.crad.2020.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Chest CT findings in asymptomatic cases with COVID-19: a systematic review and meta-analysis

Abstract: To determine the overall rate of chest imaging findings in asymptomatic cases, describe the most common patterns found, and determine the rate of later symptom development in these initially asymptomatic cases. MATERIALS AND METHODS: The PubMed and EMBASE databases were searched until 1 May 2020, for studies examining the proportion of positive chest imaging findings in asymptomatic cases diagnosed with COVID-19 and a random-effects meta-analysis of proportions was performed. Heterogeneity was assessed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…GGOs on both peripheral and subpleural lungs was the most common feature of chest CT on asymptomatic COVID-19 patients [30] and is consistent with our findings on PET/CT. Besides in asymptomatic COVID-19 patients, GGOs are also found in other infectious diseases with a variable degree of [ 18 F]FDG uptake [31].…”
Section: Discussionsupporting
confidence: 91%
“…GGOs on both peripheral and subpleural lungs was the most common feature of chest CT on asymptomatic COVID-19 patients [30] and is consistent with our findings on PET/CT. Besides in asymptomatic COVID-19 patients, GGOs are also found in other infectious diseases with a variable degree of [ 18 F]FDG uptake [31].…”
Section: Discussionsupporting
confidence: 91%
“…There is a great interest in the detection of SARS-CoV-2 infection in asymptomatic patients, as they can contribute to the viral spread with similar transmission rates as symptomatic patients [ 15 ]. There is numerous emerging evidence of patients affected by COVID-19 pneumonia who are asymptomatic or mildly symptomatic at the time of the diagnosis who show imaging features consistent with lung involvement, similarly to the case report we presented [ 16 , 17 ]. A proportion of these patients might possibly show a sudden worsening of their clinical status, resulting in acute respiratory distress syndrome (ARDS) [ 18 ].…”
Section: Discussionsupporting
confidence: 77%
“…In some cases, an initially negative CT scan within 2 d of symptom onset would become positive when repeated at a later stage[ 33 ]. Another review that investigated the CT findings in asymptomatic COVID-19 positive cases showed that among 63% of patients who had positive CT findings, 58% remained asymptomatic, however the remainder developed the symptoms[ 43 ]. Out of those who developed symptoms, 90% had previously shown positive CT scans.…”
Section: Imaging For Pulmonary Manifestations Of Covid-19mentioning
confidence: 99%